PENGARUH MODAL KERJA DAN PERPUTARAN KAS TERHADAP RETURN ON ASSETS (ROA) PADA PT. INDOFARMA (PERSERO), Tbk - Tri Wartono (Universitas Pamulang, 2018)
Return On Assets (ROA), is one of the benchmark of corporate financial performance because the amount of ROA shows the rate of return on investment as well as shows the amount of profits earned by the company. The purpose of this study is to analyze changes in working capital and cash turnover in the last ten years and its impact on ROA.Research is descriptive quantitative by using secondary data that is Balance Sheet and Profit / Loss in period 2007 until 2016. Method of analysis by using (1) ratio analysis; and (2) statistical test with SPSS 2.4 software.The results showed that simultaneously working capital and cash turnover, no significant effect on ROA, because the results of F test with a significance value of 0.102 (0.102>0.05). Meanwhile, the partial working capital variable has significant effect on ROA, t test result with significance value 0,040 (0,040<0,05). While the cash turnover has no significant effect on the ROA, t-test results show the significance value of 0.832 (0.832> 0.05).Keywords: Working Capital, Cash Turnover and ROA